2018
DOI: 10.1021/acs.analchem.8b03272
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Based Microfluidic Device for On-Chip Isolation and Detection of Tumor-Derived Exosomes

Abstract: Exosomes are membrane-enclosed phospholipid extracellular vesicles, which can act as mediators of intercellular communication. Although the original features endow tumor-derived exosomes great potential as biomarkers, efficient isolation and detection methods remain challenging. Here, we presented a two-stage microfluidic platform (ExoPCD-chip), which integrates on-chip isolation and in situ electrochemical analysis of exosomes from serum. To promote exosomes capture efficiency, an improved staggered Y-shaped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
186
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(190 citation statements)
references
References 33 publications
(58 reference statements)
1
186
0
3
Order By: Relevance
“…We highlight the need for robust study design and comprehensive data reporting, as well as testing of candidate biomarkers against current clinical gold standards in order to demonstrate the validity of this approach. We anticipate that future studies will capitalize on emerging EV isolation techniques such as microfluidic capture devices and asymmetric flow field‐flow fractionation, which may help to increase EV purity and improve assay specificity . TEVs represent an ideal target for clinical application and improvements in EV purification and characterization will ensure that this exciting field of research continues to expand over the next few years.…”
Section: Discussionmentioning
confidence: 99%
“…We highlight the need for robust study design and comprehensive data reporting, as well as testing of candidate biomarkers against current clinical gold standards in order to demonstrate the validity of this approach. We anticipate that future studies will capitalize on emerging EV isolation techniques such as microfluidic capture devices and asymmetric flow field‐flow fractionation, which may help to increase EV purity and improve assay specificity . TEVs represent an ideal target for clinical application and improvements in EV purification and characterization will ensure that this exciting field of research continues to expand over the next few years.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Xu et al, reported two‐stage microfluidic platform (ExoPCD‐chip) which integrates on‐chip isolation and in‐situ electrochemical analysis of exosomes. The developed system was utilized for the diagnosis of liver cancer patients . In addition, critical are methods to screen panels of exosome‐derived proteins, their post‐translational modifications and RNA targets.…”
Section: Discussionmentioning
confidence: 99%
“…designed an alternating current electrokinetic (ACE) microarray device, which allowed the isolation of glioblastoma‐derived exosomes from a plasma sample (30–50 μl), as well as apparently simplifying processing steps and enabling less time required. Another comprehensive exosome analysis tool and potential noninvasive diagnostic platform, ExoPCD‐chip, is a two‐stage microfluidic platform whose isolation and analysis applied for liver cancer‐derived exosomes as low as 4.39 × 10 3 particles/ml from a serum sample (30 μl) within 3.5 hr . Microfluidic chip is capable to effectively isolate exosomal ingredients as well.…”
Section: The Innovative Approaches To Detect Tumor‐derived Exosomes Fmentioning
confidence: 99%